Pesquisa do DNA viral de papilomavirus equino em lesões de placa aural - Hernández, Juliana Mira [UNESP] (2015)
Aural plaque is a disease that affects one or both equine ears characterized by well-demarcated depigmented lesions, generally cover by a whitish keratinose crust. The aim of this study was to research the presence of Equus caballus papillomavirus (EcPV) DNA in aural plaque lesions of horses from different regions of Brazil by PCR. One hundred eight biopsies and information about the lesion were collected. Was detected EcPVs DNA in 97.22% (105/108) of the tested samples. None of the samples were positive for EcPV 2 and 7. From all samples, EcPV 4 (86.67%, 91/105) was the most frequently found, followed by EcPV 3 (42.86%, 45/105), EcPV 1 (35.24%, 37/105), EcPV 6 (18.10%, 19/105) and EcPV 5 (1.90%, 2/105). When co-infection was assessed, 59.05% (62/105) of the samples were positive for more than one virus type and EcPV 3+4, EcPV 3+1 and EcPV 3+4+1, were the most frequently co-infections. No association was found between the lesion (type and distribution) and the type of papillomavirus and presence of co-infection. These results indicate that in addition to the types (EcPV 4 and 3) already detected in Brazil, was also confirmed the presence of the types 1, 5 and 6 in aural plaque lesions of equines. The results suggest the co-infection as a possible factor involved in aural plaque etiology. The EcPV 4 was the virus most detected alone or in coinfection, besides the other types also participate of equine aural plaque's etiology in Brazil